Care planning for aggression management in a specialist secure mental health service: An audit of user involvement. (19th July 2016) - Hallett, Nutmeg; Huber, Jörg W.; Sixsmith, Judith; Dickens, Geoffrey L.
Abstract: This paper describes an audit of prevention and management of violence and aggression care plans and incident reporting forms which aimed to: (i) report the compliance rate of completion of care plans; (ii) identify the extent to which patients contribute to and agree with their care plan; (iii) describe de‐escalation methods documented in care plans; and (iv) ascertain the extent to which the de‐escalation methods described in the care plan are recorded as having been attempted in the event of an incident. Care plans and incident report forms were examined for all patients in men's and women's mental health care pathways who were involved in aggressive incidents between May and October 2012. In total, 539 incidents were examined, involving 147 patients and 121 care plans. There was no care plan in place at the time of 151 incidents giving a compliance rate of 72%. It was documented that 40% of patients had contributed to their care plans. Thematic analysis of de‐escalation methods documented in the care plans revealed five de‐escalation themes: staff interventions, interactions, space/quiet, activities and patient strategies/skills. A sixth category, coercive strategies, was also documented. Evidence of adherence to de‐escalation elements of the care plan was documented in 58% of incidents. The reasons for the low compliance rate and very low documentation of patient involvement need further investigation. The inclusion of coercive strategies within de‐escalation documentation suggests that some staff fundamentally misunderstand de‐escalation.